The Influence of Company Size, Leverage and Profitability on the Company Value of Food and Beverage Companies on the IDX for the 2019-2022 Period - Gea, Delvita Sari; Sinulingga, Windhy Paskani; Ginting, Hardi Ronanda; amir, Afriza; BibRahmani, Nur Ahmadi (International Journal Of Economics Social And Technology (IJEST), 2024)
The aim of this research is to find out Influence Size Companies, Leverage and Profitability in Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this research was 18 companies using sample of 17 companies. This type of research uses Approach Quantitative and engineering analysis bye use analysis statistics Descriptive. This type of research concludes that Size company influential positive and not significant to mark company to company food and beverage sector listed on the stock exchange Indonesia in 2019-2022, Leverage is influential positive and significant to mark company to company food and beverage sector listed on the ei stock exchange feik Indonesia 2019-2022, Profitability influential positive and significant to mark company to company food and beverage sector listed on the stock exchange Indonesia in 2019-2022, Company Size, Leverage, Includes Profitability give influence as much as 69.08 % Against mark company to company sector food and bei veiraigei listed on the bursai effective Indonesia in 2019-2022